Cross-sectoral coordination for sustainable solutions in Croatia: The (meta) governance of energy efficiency. (December 2016) - Christopoulos, Stamatios; Demir, Cansu; Kull, Michael
Abstract: Increasing the energy efficiency not only requires the improvement of current technologies, but also advancement of and more coherent institutional governance. This paper captures the major structural and organisational elements of institutional governance in place for promoting energy efficiency. Looking at Croatia – one of the most successful cases of energy efficiency programming of the past decade – the paper zooms in on governance coordination (metagovernance) between actors from different sectors and operating at multiple levels. By showcasing the positive implications of the programme, the authors contribute to the debate concerned with identifying better institutional frameworks to attain sustainable development. The programme showed effective governance through vertical and horizontal coordination among institutions and stakeholders resulting in simultaneous social and economic development and improved energy efficiency in public buildings. Through the case of Croatia, this study identifies how metagovernance has supported coordination among actors aiming to create sustainable development in general and how metagovernance functions in energy efficiency related projects, in particular. The paper also sheds light on communication frameworks of governance coordination and institutional constraints lying at the heart of the vagueness of sustainable development. It also discusses private sector involvement to achieve better institutional framework to attain sustainable development. Highlights: This study identified how metagovernance has supported coordination among actors. State played a key role in the coordination by acting as a catalyst. UNDP acted as a mediator between government and society for capacity building. Public authorities are less likely to continue activities without external support. Private sector's knowledge and resources are crucial to support project objectives.